Solid state battery negative electrode and manufacturing method thereof
By using rubber-based adhesives that vulcanize the crosslinked structure in the negative electrode of the solid-state battery, the problem of contact deterioration of electrode materials caused by volume changes in solid-state batteries is solved, and the battery performance and life are improved.
Patent Information
- Application Number
- CN202410442606.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-22
- Filing Date
- 2024-04-12
- Publication Date
- 2025-02-25
AI Technical Summary
During the charging and discharging process, solid-state batteries cause electrode material contact deterioration, silicon pulverization and battery life shorten.
By using vulcanizing a rubber-based adhesive to form a crosslinked structure, the electrode adhesion and contact between the solid electrolyte and the active substance are enhanced, a solid-state battery negative electrode with improved battery performance and life is prepared.
It improves the mechanical properties and cycling characteristics of the electrode, extends the service life of the solid-state battery, and enhances the charging and discharging capabilities of the battery.
Smart Images

Figure CN119517985A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0110162 filed in the Korean Intellectual Property Office on August 22, 2023, the disclosure of which is incorporated herein by reference. Technical Field
[0003] The present invention relates to a solid-state battery negative electrode comprising a vulcanized binder and a method for manufacturing the same. Background Art
[0004] Rechargeable / dischargeable secondary batteries have been used as large-capacity power storage batteries for electric vehicles, power storage systems, etc., or as compact, high-performance energy sources for portable electronic devices such as mobile phones, video cameras, and notebook computers. Lithium-ion batteries are typical secondary batteries that have a larger capacity per unit area, a lower self-discharge rate, and a smaller memory effect than nickel-manganese batteries or nickel-cadmium batteries, and therefore have higher practicality.
[0005] However, lithium-ion batteries use liquid electrolytes containing organic solvents, so it is difficult to provide battery stability due to leakage, impact, etc. caused by the use of highly volatile organic solvents. Therefore, in order to ensure the safety of lithium-ion batteries, solid-state batteries using solid electrolytes instead of liquid electrolytes have been actively studied.
[0006] On the other hand, unlike typical lithium-ion batteries, solid-state batteries have the advantage that the battery is provided with a solid electrolyte, indicating that no separator is required and the heat generation is low, so the risk of explosion is small. However, compared with the case of using a liquid electrolyte, the solid electrolyte has poor chemical stability, low price competitiveness, and low energy density, so it has not yet been commercialized.
[0007] To address these issues, research on solid-state batteries that improve energy density by applying silicon negative electrode active materials has been actively carried out. However, solid-state batteries using silicon negative electrode active materials have some limitations, such as significant volume changes caused by repeated shrinkage and expansion during charging and discharging. Drastic volume changes weaken the degree of contact between constituent materials in the electrode such as active material particles, conductive material particles, and electrolytes, resulting in deterioration of the conductive network, charge and discharge performance, and capacity with charge and discharge cycles. In addition, volume changes can cause silicon pulverization due to stress at the interface, and when high output currents are applied, uneven volume changes can cause rapid deterioration of battery life.
[0008] Therefore, it is necessary to develop a technology that can maintain the excellent performance of solid-state batteries and increase the service life of solid-state batteries by applying silicon negative electrode active materials. Summary of the invention
[0009] Embodiments of the present invention provide a solid-state battery negative electrode and a method for manufacturing the same, which improves battery life by enhancing electrode adhesion and contact between a solid electrolyte and an active material by applying a binder that forms a cross-linked structure through sulfurization.
[0010] The cross-linked structure may be formed into a three-dimensional network structure as chains of the rubber-based binder are connected.
[0011] The negative electrode active material particles may be connected by a rubber-based binder, and the rubber-based binder may be formed by containing -(S) n -linker, and n is an integer of 1 or greater.
[0012] The diameter of silicon-coated graphite may be about 8 μm to about 20 μm.
[0013] The rubber-based binder may include butadiene rubber. In some embodiments, the rubber-based binder may include at least one selected from the group consisting of styrene-butadiene rubber (SBR), nitrile rubber (NBR), butadiene rubber (BR), ethylene-propylene-diene rubber (EPDM), acrylonitrile-butadiene-styrene copolymer (ABS), styrene-isoprene-styrene (SIS), styrene-butadiene-styrene (SBS), acrylic rubber (AR) and mixtures thereof.
[0014] The solid-state battery negative electrode may further include a solid electrolyte. The solid electrolyte may include a sulfide-based solid electrolyte.
[0015] According to an embodiment of the present invention, a method for manufacturing a solid-state battery negative electrode is provided. The method includes coating a slurry on a current collector, drying and vulcanizing, wherein the slurry includes: a binder mixture including a rubber-based binder and a vulcanizing agent; negative electrode active material particles including silicon-coated graphite; and a solid electrolyte.
[0016] The adhesive mixture may include 100 parts by weight of a rubber-based adhesive and about 4.5 to 20 parts by weight of a vulcanizing agent.
[0017] The slurry may include 100 parts by weight of the solid electrolyte and about 0.2 to 1.5 parts by weight of the sulfiding agent.
[0018] The vulcanizing agent may include 1 part by weight of sulfur (S 2) and a vulcanization accelerator of about 2 to 5 parts by weight. The vulcanization accelerator may include at least one selected from the group consisting of 2-mercaptobenzothiazole (MBT), tetra(isobutyl)thiuram disulfide (TiBTD), zinc dibutyldithiocarbamate (ZnDBC), N,N-diethylthiourea (DETU), caprolactam disulfide (CLD), N-cyclohexyl-2-benzothiazolesulfenamide, tetramethylthiuram disulfide and mixtures thereof. The rubber-based binder may include at least one selected from the group consisting of styrene-butadiene rubber (SBR), nitrile rubber (NBR), butadiene rubber (BR), ethylene propylene diene rubber (EPDM), acrylonitrile-butadiene-styrene copolymer (ABS), styrene-isoprene-styrene (SIS), styrene-butadiene-styrene (SBS), acrylic rubber (AR) and mixtures thereof.
[0019] The solid electrolyte may include a sulfide-based solid electrolyte.
[0020] The slurry may be obtained by dry-mixing negative electrode active material particles and a solid electrolyte and further mixing with a binder mixture and a solvent.
[0021] The binder mixture may be prepared by stirring a mixture including the rubber-based binder and the vulcanizing agent for about 12 to 36 hours.
[0022] Drying may be performed at about 80° C. to 100° C. for about 1 to 3 hours, and vulcanization may be performed at about 130° C. to 150° C. for about 1 to 30 minutes.
[0023] In some embodiments, a solid-state battery may include a solid-state battery anode.
[0024] In some embodiments, a vehicle including a solid-state battery may be provided.
[0025] According to another embodiment of the present invention, there is provided a method for manufacturing a solid-state battery negative electrode, the method comprising the following steps: applying a binder mixture comprising 100 parts by weight of a rubber-based binder and 4.5 to 20 parts by weight of a vulcanizing agent, and a negative electrode slurry comprising negative electrode active material particles and a solid electrolyte, drying and vulcanizing. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The above and other embodiments, features and other advantages of the present invention will be more clearly understood from the following detailed description taken in conjunction with the accompanying drawings, in which:
[0027] Figure 1 is a schematic diagram showing a negative electrode of a solid-state battery according to an embodiment of the present invention;
[0028] Figure 2is a schematic diagram showing a binder having a cross-linked structure formed by vulcanization;
[0029] Figure 3 is a graph showing the cycle characteristics evaluation results of Examples 1 to 3 and Comparative Example 1. DETAILED DESCRIPTION
[0030] Hereinafter, a solid-state battery negative electrode and a method for manufacturing the same will be described in detail so that those skilled in the art to which the present invention pertains can easily implement the present invention.
[0031] It is understood that the term "vehicle" or "vehicular" or other similar terms as used herein generally include motor vehicles, such as passenger vehicles including sport utility vehicles (SUVs), buses, trucks, various commercial vehicles, watercraft including various ships and boats, aircraft, etc., and include hybrid vehicles, electric vehicles, plug-in hybrid vehicles, hydrogen-powered vehicles, and other alternative fuel (e.g., fuels derived from resources other than petroleum) vehicles. As referred to herein, a hybrid vehicle is a vehicle having two or more power sources, such as gasoline-powered and electric-powered vehicles.
[0032] The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. As used herein, the singular forms "one", "an" and "the" are also intended to include plural forms, unless the context clearly indicates otherwise. These terms are only used to distinguish a component from another component, and these terms do not limit the properties, order or sequence of the components. It will be further understood that the terms "include" and / or "comprising" used in this specification indicate the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or their groups. As used herein, the term "and / or" includes any one and all combinations of one or more related listed items. Throughout the specification, unless there is a clear contrary description, the word "include" and variants such as "include" or "include with" will be understood to imply the inclusion of the elements, without excluding any other elements. In addition, the terms "unit", "-er", "-device" and "module" described in this specification refer to units for processing at least one function and operation, and can be implemented by hardware components or software components and their combinations.
[0033] Although the exemplary embodiments are described as using multiple units to perform the exemplary processes, it is understood that the exemplary processes can also be performed by one or more modules. In addition, it is understood that the term controller / control unit refers to a hardware device including a memory and a processor, and is specifically programmed to run the processes described herein. The memory is configured to store the modules, and the processor is specifically configured to execute the modules to perform one or more processes described further below.
[0034] In addition, the control logic of the present invention may be implemented as a non-transitory computer-readable medium on a computer-readable medium containing executable program instructions executed by a processor, a controller, etc. Examples of computer-readable media include, but are not limited to, ROM, RAM, compact disk (CD)-ROM, magnetic tape, floppy disk, flash drive, smart card, and optical data storage device. The computer-readable recording medium may also be distributed in a networked computer system so that the computer-readable medium is stored and executed in a distributed manner, for example, by a telematics server or a controller area network (CAN).
[0035] Unless otherwise specified or apparent from the context, as used herein, the term "about" is to be understood as being within the normal tolerance range in the art, such as within 2 standard deviations of the mean. "About" may be understood as being within 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05%, or 0.01% of a specified value. Unless the context clearly indicates otherwise, all numerical values provided herein are modified by the term "about".
[0036] As used herein, the term "solid-state battery" refers to a rechargeable secondary battery that includes a solid electrolyte such as a gel or polymer (cured), which may include an ionic polymer and other electrolyte components for transferring ions between the electrodes of the battery.
[0037] A solid-state battery negative electrode according to an embodiment of the present invention may include negative electrode active material particles containing silicon-coated graphite and a rubber-based binder, and the rubber-based binder may have a cross-linked structure formed by a vulcanization treatment.
[0038] Carbon, a typical negative electrode active material, can store 1 lithium ion for every 6 carbon atoms when storing lithium ions, while silicon contained in silicon-coated graphite can store about 4.4 lithium ions for each silicon atom when storing lithium ions. Therefore, when using negative electrode active material particles containing silicon-coated graphite, solid-state batteries can improve performance by increasing energy density.
[0039] On the other hand, silicon rapidly expands or contracts in volume during charging and discharging, which may weaken the contact between materials in the electrode, resulting in short circuit of lithium ion paths and pulverization of silicon. Therefore, the present invention aims to improve the electrode adhesion and the interface contact between the solid electrolyte and the active material by using a vulcanized binder.
[0040] Figure 1 is a schematic diagram showing a solid-state battery negative electrode according to an embodiment of the present invention.
[0041] Reference Figure 1 It can be seen that the rubber-based binder connects the negative electrode active material particles, improves the bonding strength between the negative electrode active material and the solid electrolyte, and is distributed together with the negative electrode active material and the solid electrolyte, so that the slurry containing the negative electrode active material and the solid electrolyte can be uniformly coated on the current collector, and the rubber-based binder has a cross-linked structure formed by vulcanization.
[0042] The solid-state battery negative electrode according to an embodiment of the present invention may include a rubber-based binder, and the rubber-based binder may have a cross-linked structure formed by vulcanization. As the rubber-based binder chains are connected, the cross-linked structure may form a three-dimensional network structure. In this case, the formation of a three-dimensional network structure represents a structure in which the atoms included in the chain constituting the rubber-based binder are connected to the atoms included in another chain constituting the rubber-based binder through a connecting group containing a sulfur atom (S).
[0043] Figure 2 is a schematic diagram showing a binder having a cross-linked structure formed by vulcanization.
[0044] Reference Figure 2 It can be seen that the chains of the rubber-based adhesive are connected by connecting groups due to vulcanization to form a three-dimensional network structure.
[0045] On the other hand, the rubber-based binder connecting the negative electrode active material particles can be connected through a connecting group containing -(S)n-. In this case, n is an integer of 1 or more. That is, the connecting group can include one sulfur atom or multiple sulfur atoms.
[0046] The diameter of the silicon-coated graphite may be 8 μm to 20 μm, preferably 8 μm to 10 μm. When the silicon-coated graphite having a diameter within the above range is used, better charge / discharge capability may be obtained, thereby improving initial efficiency and charging performance.
[0047] Rubber-based adhesive as described herein can include multiple materials.For example, rubber-based adhesive can include styrene-butadiene rubber, acrylic styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylonitrile-butadiene-styrene rubber, acrylic rubber, butyl rubber, fluororubber or their combination.In some respects, rubber-based adhesive can include natural rubber, butyl rubber, brominated butyl rubber, chlorinated butyl rubber, styrene-isoprene-styrene (SIS), styrene-ethylene-butylene-styrene-based rubber, acrylonitrile-butadiene-styrene-based rubber, polybutadiene-based rubber, acrylonitrile-butadiene rubber, styrene-butadiene rubber, styrene-butadiene-styrene-based rubber (SBS) and ethylene propylene diene monomer (EPDM)-based rubber one or more.
[0048] In certain preferred aspects, the rubber-based adhesive may include at least one selected from the group consisting of styrene-butadiene rubber (SBR), nitrile rubber (NBR), butadiene rubber (BR), ethylene propylene diene rubber (EPDM), acrylonitrile-butadiene-styrene copolymer (ABS), styrene-isoprene-styrene (SIS), styrene-butadiene-styrene (SBS), acrylic rubber (AR) and mixtures thereof. Preferably, the rubber-based adhesive may include at least one selected from the group consisting of styrene-butadiene rubber (SBR), nitrile rubber (NBR), butadiene rubber (BR) and mixtures thereof.
[0049] The rubber-based adhesive can suitably include one or more different materials.At least a portion of the rubber-based adhesive will include the material that is regarded as rubber-like material, such as above-mentioned one or more materials.For example, in some respects, at least 10 % by weight, 20 % by weight, 30 % by weight, 40 % by weight, 50 % by weight, 60 % by weight, 70 % by weight, 80 % by weight, 90 % by weight, 95 % by weight, 98 % by weight or 99 % by weight of the rubber-based adhesive component gross weight will be made up of one or more rubber-like materials, such as one or more above-mentioned materials.
[0050] The solid-state battery negative electrode according to an embodiment of the present invention may further include a solid electrolyte. Therefore, compared with a secondary battery using a liquid electrolyte, sulfur elution can be suppressed, thereby further improving electrode adhesion and the interface contact force between the solid electrolyte and the active material.
[0051] The solid electrolyte may include a sulfide-based solid electrolyte. The solid electrolyte may be in the form of a powder or a molded article. The solid electrolyte in the form of a molded article may be in the form of, for example, a pellet, a sheet, or a film, but is not necessarily limited thereto and may also be in various forms depending on the intended use.
[0052] Next, a method for manufacturing a solid-state battery negative electrode according to another embodiment of the present invention will be described in detail.
[0053] The method for manufacturing a solid-state battery negative electrode according to an embodiment of the present invention may include the following steps: applying a binder mixture comprising 100 parts by weight of a rubber-based binder and 4.5 to 20 parts by weight of a vulcanizing agent, as well as a negative electrode slurry of negative electrode active material particles and a solid electrolyte, drying and vulcanizing.
[0054] The adhesive mixture may include 100 parts by weight of the rubber-based adhesive and 4.5 to 20 parts by weight of the vulcanizing agent, preferably 100 parts by weight and 5 to 20 parts by weight, more preferably 100 parts by weight and 10 to 20 parts by weight.
[0055] Adding a rubber-based binder and a vulcanizing agent within the above range can improve the electrode adhesion and the interfacial contact force between the solid electrolyte and the active material, improve the mechanical properties, and further increase the life of the solid-state battery through excellent cycle characteristics.
[0056] The slurry for the negative electrode may include 100 parts by weight of a solid electrolyte and 0.2 to 1.5 parts by weight of a vulcanizing agent, preferably 100 parts by weight of a solid electrolyte and 0.29 to 1.5 parts by weight of a vulcanizing agent, more preferably 100 parts by weight of a solid electrolyte and 0.29 to 1.17 parts by weight of a vulcanizing agent, more preferably 100 parts by weight of a solid electrolyte and 0.59 to 1.5 parts by weight of a vulcanizing agent, most preferably 100 parts by weight of a solid electrolyte and 0.59 to 1.17 parts by weight of a vulcanizing agent.
[0057] Adding the solid electrolyte and the vulcanizing agent within the above range can make the negative electrode slurry evenly coated on the current collector and can improve the electrode adhesion, thereby increasing the service life of the solid-state battery.
[0058] The vulcanizing agent may include 1 part by weight of sulfur (S 2 ) and 2 to 5 parts by weight of a vulcanization accelerator, preferably 1 part by weight of sulfur (S 2 ) and 2 to 4 parts by weight of a vulcanization accelerator, more preferably 1 part by weight of sulfur (S 2 ) and 3 to 4 parts by weight of a vulcanization accelerator.
[0059] Including sulfur and the vulcanization accelerator within the above range can sufficiently form a crosslinking structure connecting rubber-based binder chains and can also prevent brittleness due to an excessive crosslinking reaction.
[0060] Adding a vulcanization accelerator can promote the crosslinking of sulfur between rubber-based adhesive chains, and the vulcanization accelerator can include at least one selected from the group consisting of 2-mercaptobenzothiazole (MBT), tetra(isobutyl)thiuram disulfide (TiBTD), zinc dibutyldithiocarbamate (ZnDBC), N,N-diethylthiourea (DETU), caprolactam disulfide (CLD), N-cyclohexyl-2-benzothiazolesulfenamide, tetramethylthiuram disulfide and mixtures thereof.
[0061] The rubber-based adhesive may include at least one selected from the group consisting of styrene-butadiene rubber (SBR), nitrile rubber (NBR), butadiene rubber (BR), ethylene propylene diene monomer (EPDM), acrylonitrile-butadiene-styrene copolymer (ABS), styrene-isoprene-styrene (SIS), styrene-butadiene-styrene (SBS), acrylic rubber (AR) and mixtures thereof. Preferably, the rubber-based adhesive may include at least one selected from the group consisting of styrene-butadiene rubber (SBR), nitrile rubber (NBR), butadiene rubber (BR) and mixtures thereof.
[0062] In addition, the solid electrolyte may include a sulfide-based solid electrolyte and may be in the form of a powder or a molded article. The solid electrolyte in the form of a molded article may be in the form of, for example, particles, flakes or films, but is not necessarily limited thereto and may take various forms depending on the intended use.
[0063] The slurry for the negative electrode can be obtained by dry mixing the negative electrode active material particles and the solid electrolyte and further mixing with the binder mixture and the solvent. In this case, the mixing can be performed using a planetary disperser (P / D) mixer to ensure uniformity, but is not limited thereto.
[0064] The binder mixture may be prepared by stirring a mixture containing the rubber-based binder and the vulcanizing agent for 12 to 36 hours, preferably 24 to 36 hours, more preferably 24 hours, for uniform mixing.
[0065] Drying may be performed at 80° C. to 100° C. for 1 to 3 hours, preferably at 90° C. for 1 to 2 hours, and vacuum drying (V / D) may be performed to shorten the process time, but embodiments of the present invention are not limited thereto.
[0066] Vulcanization may be performed at 130° C. to 150° C. for 1 to 30 minutes, preferably at 140° C. for 20 to 30 minutes. Vulcanization performed within the above vulcanization temperature and time range may fully form a crosslinked structure and may also prevent brittleness caused by an excessive crosslinking reaction.
[0067] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are provided to help understand the present invention, and the scope of the present invention is not limited to these examples in any sense.
[0068] <Example 1> Manufacturing of solid-state battery negative electrode 1
[0069] The adhesive mixture containing a rubber-based adhesive comprising 100 parts by weight of butadiene rubber (BR) and 20 parts by weight of a vulcanizing agent was stirred by a P / D (planetary disperser) mixer for 24 hours to prepare an adhesive mixture. In this case, the vulcanizing agent included 1 part by weight of sulfur (S 2 ) and 3 parts by weight of a vulcanization accelerator, and 2-mercaptobenzothiazole (MBT) is used as a vulcanization accelerator.
[0070] Subsequently, the negative electrode active material particles and the sulfide-based solid electrolyte are dry-mixed by a P / D (planetary disperser) mixer, and then the solvent is further mixed with the binder mixture to prepare a negative electrode slurry. In this case, the average diameter (D 50 ) as the negative electrode active material particles, and butyl butyrate as the solvent. In addition, the solid electrolyte and the sulfiding agent were contained in a ratio of 100 parts by weight of the solid electrolyte and 1.17 parts by weight of the sulfiding agent.
[0071] Subsequently, the negative electrode slurry was coated on the current collector, followed by vacuum drying (V / D) at 90°C for 2 hours and sulfurization at 140°C for 20 minutes to prepare a solid-state battery negative electrode.
[0072] <Example 2> Manufacturing of solid-state battery negative electrode 2
[0073] The manufacturing method of the solid-state battery negative electrode is the same as that of Example 1, except that a binder mixture containing 100 parts by weight of a rubber-based binder and 5 parts by weight of a vulcanizing agent is used, and the solid electrolyte is included in an amount of 100 parts by weight and the vulcanizing agent is included in an amount of 0.29 parts by weight.
[0074] <Example 3> Manufacturing of solid-state battery negative electrode 3
[0075] The manufacturing method of the solid-state battery negative electrode is the same as that of Example 1, except that an adhesive mixture containing 100 parts by weight of a rubber-based adhesive and 10 parts by weight of a vulcanizing agent is used, and the solid electrolyte is included in an amount of 100 parts by weight and the vulcanizing agent is included in an amount of 0.59 parts by weight.
[0076] <Comparative Example 1> Production of a negative electrode for a solid-state battery 4
[0077] The method for manufacturing the solid-state battery negative electrode is the same as that in Example 1, but without adding a vulcanizing agent.
[0078] <Experimental Example 1> Evaluation of electrode adhesion of solid-state battery negative electrode
[0079] In order to evaluate the electrode adhesion of the solid-state battery negative electrode, the 180° peel strength of the solid-state battery negative electrode according to Examples 1 to 3 and Comparative Example 1 was measured using a universal testing machine (UTM). In this case, the 180° peel strength is the average peel strength measured in a section with a displacement of 20 mm to 50 mm.
[0080] In the 180° peel strength evaluation, the adhesive force of Example 1 was observed to be 1.21 gf / mm, the adhesive force of Example 2 was observed to be 0.28 gf / mm, the adhesive force of Example 3 was observed to be 1.09 gf / mm, and the adhesive force of Comparative Example 1 was 0.02 gf / mm. That is, Examples 1 to 3 using the rubber-based adhesive forming a cross-linked structure by vulcanization were observed to have greater electrode adhesion than Comparative Example 1 using no vulcanizing agent.
[0081] <Experimental Example 2> Evaluation of Cycling Characteristics of Solid-State Battery Negative Electrode
[0082] In order to evaluate the cycle characteristics of the solid-state battery negative electrode, the following Table 1 shows the discharge capacity, charge capacity and capacity retention rate of Examples 1 to 3 and Comparative Example 1 after 20 cycles of charge and discharge.
[0083] [Table 1]
[0084]
[0085] Referring to Table 1, it can be seen that the electrode adhesion and the interfacial contact force between the solid electrolyte and the active material of Examples 1 to 3 using a rubber-based binder that forms a cross-linked structure by vulcanization are improved, thereby improving the life of the battery, but the battery life of Comparative Example 1 in which no vulcanizing agent is added is relatively short.
[0086] Figure 3 : is a graph showing the cycle characteristics evaluation results of Examples 1 to 3 and Comparative Example 1.
[0087] Reference Figure 3 As described above, it can be seen that, compared with Comparative Example 1, the capacity retention rate of Examples 1 to 3 using the rubber-based binder forming a cross-linked structure by vulcanization decreases less with the number of cycles.
Claims
1. A solid-state battery negative electrode, comprising: Negative electrode active material particles, wherein the negative electrode active material particles include silicon-coated graphite; as well as Rubber-based adhesives, Wherein, the rubber-based adhesive has a cross-linked structure.
2. The solid-state battery negative electrode according to claim 1, wherein: The cross-linked structure of the rubber-based adhesive is produced by vulcanization.
3. The solid-state battery negative electrode according to claim 1, wherein: The cross-linked structure is formed into a three-dimensional network structure as chains of the rubber-based binder are connected.
4. The solid-state battery negative electrode according to claim 1, wherein: The negative electrode active material particles are connected by the rubber-based binder, and The rubber-based adhesive comprises: n -linking group, and n is an integer of 1 or greater.
5. The solid-state battery negative electrode according to claim 1, wherein: The diameter of the silicon-coated graphite is 8 μm to 20 μm.
6. The solid-state battery negative electrode according to claim 1, wherein: The rubber-based adhesive includes butadiene rubber.
7. The solid-state battery negative electrode according to claim 1, wherein: The rubber-based binder includes at least one selected from the group consisting of styrene-butadiene rubber (SBR), nitrile rubber (NBR), butadiene rubber (BR), ethylene-propylene-diene rubber (EPDM), acrylonitrile-butadiene-styrene copolymer (ABS), styrene-isoprene-styrene (SIS), styrene-butadiene-styrene (SBS), acrylic rubber (AR) and mixtures thereof. The solid-state battery negative electrode according to claim 1 , further comprising a solid electrolyte.
9. The solid-state battery negative electrode according to claim 8, wherein: The solid electrolyte includes a sulfide-based solid electrolyte.
10. A method for manufacturing a solid-state battery negative electrode, the method comprising: The slurry is coated on the current collector, dried and sulfurized, Wherein, the slurry comprises: An adhesive mixture comprising a rubber-based adhesive and a vulcanizing agent, Negative electrode active material particles comprising silicon-coated graphite, and Solid electrolyte.
11. The method according to claim 10, wherein: The adhesive mixture includes 100 parts by weight of the rubber-based adhesive and about 4.5 to 20 parts by weight of the vulcanizing agent.
12. The method according to claim 10, wherein: The slurry includes 100 parts by weight of the solid electrolyte and 0.2 to 1.5 parts by weight of the sulfiding agent.
13. The method according to claim 10, wherein: The vulcanizing agent comprises 1 part by weight of sulfur, namely S2, and 2 to 5 parts by weight of a vulcanization accelerator.
14. The method according to claim 13, wherein: The vulcanization accelerator includes at least one selected from the group consisting of 2-mercaptobenzothiazole (MBT), tetra(isobutyl)thiuram disulfide (TiBTD), zinc dibutyldithiocarbamate (ZnDBC), N,N-diethylthiourea (DETU), caprolactam disulfide (CLD), N-cyclohexyl-2-benzothiazolesulfenamide, tetramethylthiuram disulfide and mixtures thereof.
15. The method according to claim 10, wherein: The rubber-based binder includes at least one selected from the group consisting of styrene-butadiene rubber (SBR), nitrile rubber (NBR), butadiene rubber (BR), ethylene-propylene-diene rubber (EPDM), acrylonitrile-butadiene-styrene copolymer (ABS), styrene-isoprene-styrene (SIS), styrene-butadiene-styrene (SBS), acrylic rubber (AR) and mixtures thereof.
16. The method according to claim 10, wherein: The solid electrolyte includes a sulfide-based solid electrolyte.
17. The method according to claim 10, wherein: The slurry is obtained by dry-mixing the negative electrode active material particles and the solid electrolyte and further mixing with the binder mixture and a solvent.
18. The method according to claim 10, wherein: The binder mixture is prepared by stirring a mixture including the rubber-based binder and the vulcanizing agent for 12 to 36 hours.
19. A solid-state battery, comprising the solid-state battery negative electrode according to claim 1.
20. A vehicle comprising the solid-state battery according to claim 19.
Citation Information
Cited By
Silicon-carbon negative electrode gel material, lithium ion battery negative electrode and preparation method thereof, lithium ion battery and battery system
CN120767315A
Composite solid electrolyte, preparation method thereof and all-solid-state battery
CN121035333A
Composite solid electrolyte, method for preparing the same, and all-solid-state battery
CN121035333B